Application of the iteration-interpolation method to solution of mathematical physics problems - Grishin, Anatoliy Mikhailovich; Zinchenko, Vladislav Ivanovich; Efimov, Konstantin Nikolaevich; Yakimov, Anatoliy Stepanovich (Computational Continuum Mechanics, 2008)
Based on the iteration-interpolation method, an algorithm for solving the parabolic differential equation and a differential scheme for numerical solution of the boundary layer equation applicable to a wide range of Mach and Reynolds numbers have been developed. The scheme is unconditionally stable with second-order approximation inaccuracy relative to the spatial coordinate and first-order approximation inaccuracy relative to the march coordinate. The practical convergence of the differential scheme has been considered using the trial function method.